Comparative study of MPC and LQC with disturbance rejection control for heavy vehicle rollover prevention in an inclement environment - Yakub, F. (Korean Society of Mechanical Engineers, 2016)
This paper compares the Model predictive control (MPC) and Linear quadratic control (LQC) of heavy vehicles via active front steering for rollover prevention in inclement environments. In both control methods, a Disturbance rejection control (DRC) that negates the effects of wind and road bank acting on the vehicle is designed. Load transfer ratio (LTR) is applied to judge rollover by mitigating the absolute value of LTR as much as possible. We tested and compared two different controllers, i) MPC with DRC and ii) LQC with DRC. Two types of environmental conditions were considered, i) typhoon and ii) typhoon on a bumpy road. The simulation results demonstrate that MPC was more successfully implemented than LQC during LTR suppression. This paper also proposes an MPC for coordination of active rear steering and differential braking control maneuvers to prevent rollover in inclement environments. For a feasible comparison, the LQC controller was designed using the same approach adopted for the MPC controller. Results show the proposed coordinated control yields better performance for rollover prevention than LQC.